Liver histopathology of baung fish, Hemibagrus nemurus (Valenciennes, 1840) and the level of Pb in Siak River, Pekanbaru, Riau, Sumatra - Yusfiati; Onni Yesika Hutabarat (LPPM Universitas Negeri Jakarta, 2024)
The high levels of Pb in the water will affect the structure of fish liver organs. This study aims to determine changes in the macroscopic and microscopic structure of the liver organ of baung fish (Hemibagrus nemurus), as well as Pb levels in Siak River. Fish and river water samples were taken from Lima Puluh and Rumbai Pesisir Subdistrict. Histological preparation using paraffin method and HE stain. Pb levels using the Atomic Absorption Spectrophotometry (AAS) method. The macroscopic structure of the liver in Location 1 was yellowish red and Location 2 was brownish red. The average percentage of liver tissue damage in Location 1 was parenchymal degeneration (1.68%), hydropic degeneration (1.46%), fatty degeneration (30.77%), and necrosis (39.24%). Location 2 was parenchymal degeneration (1.20%), hydropic degeneration (1.35%), fatty degeneration (16%), and necrosis (21.70%). Fatty degeneration and necrosis damage are medium, and other damage is slight. The Pb level of Siak River in Pekanbaru City in 2024 was 0.113 mg/L (Location 1) and 0.072 mg/L (Location 2). Pb levels in Siak River have exceeded the standard limit of Pb in waters. High levels of Pb in the Siak River can damage the structure of fish liver tissue.